Associations of Lipoprotein Lipase S447X and Apolipoprotein E Genotypes with Low-density Lipoprotein Subfractions in Turkish Patients with Coronary Artery Disease - (:unkn) unknown (INT INST ANTICANCER RESEARCH, 2009)
Background: This study investigated associations of specific lipoprotein lipase (LPL) S447X and apolipoprotein (Apo)E allelic patterns with low-density lipoprotein (LDL) size and subfraction profiles in patients with coronary artery disease (CAD) and health), individuals. Patients and Methods: Forty-one cases with CAD and 23 controls were compared regarding the occurrence of the Ser -> Stop codon of the LPL and ApoE polymorphism. Polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) techniques were utilized to perform genotyping, and LDL size and subfractions were assessed by a high-resolution, nongradient polyacrylamide gel electrophoresis technique. Results: The lowest small dense (sd) LDL level was observed for the homozygous LPLX447 genotype (6.00 +/- 4.00 mg/dl) while the highest sdLDL level was observed for LPLX447(+)/ApoE4(+) carriers (14.33 +/- 20.55 mg/dl) in the patient group. No protective effect of LPLX447 allele on the atherogenic LDL profile was observed when it was together with the ApoE4 allele. Furthermore, the detrimental effect of LPLS447 on the atherogenic LDL profile increased when it was present together with the ApoE4 allele. Conclusion: The X447 allele of the LPL gene may protect from atherogenic LDL subfraction, although this effect is small. We suggest that the S447X polymorphism of the LPL gene may modify the risk of atherogenic sdLDL fraction in at? ApoE-dependent fashion.
Keywords: Lipoprotein lipase; apolipoprotein E; lipoproteins; LDL size; genetics; coronary artery disease; E POLYMORPHISM; HEART-DISEASE; MYOCARDIAL-INFARCTION; PLASMA-LIPOPROTEIN; GENE POLYMORPHISMS; HDL-CHOLESTEROL; POPULATION; VARIANTS; RISK; LPL